The Effect Of Acidity And Concentration Of Yeast Starter On Quality Of Alcoholic Drink From Soursop - Agam CF Silaen; Sentosa Ginting; Ismed Suhaidi (Jurnal Rekayasa Pangan dan Pertanian, 2013)
The aim of this research was to know the effect of acidity and yeast cencentration on quality of alcoholic drink from soursop. This research have been performed using factorial Completely Randomized Design with two factors i.e: acidity (P) : (3, 4, 5 and 6) and yeast starter concentration (K) : (2%, 3%, 4% dan 5%). Parameters analysed were total soluble solid, pH, total alcohol, organoleptic values of color, flavour and taste. The results showed that acidity had highly significant effect on all parameters except on color, flavour and taste. Yeast starter concentration had highly significant effect on all parameters. Interaction of acidity and yeast starter concentration had highly significant on total alcohol, had significantly effect on total soluble solid, pH and were not significantly effect the color, flavour and taste. Acidity of 4 and yeast concentration of 5% gave the best quality of alcoholic drink from soursop. . Key words : acidity, alcoholic drink, soursop, yeast starter concentration